Odpowiedź:
a1 = 5[tex]x^{2}[/tex]-x+3
a2 = 2x
a3 = x-4
a2= a1+r --> 5[tex]x^{2}[/tex]x+3+r = 2x
a3=a1+2r --> 5[tex]x^{2}[/tex]-x+3+2r = x-4
2x=5[tex]x^{2}[/tex]-x+3+r
x=5[tex]x^{2}[/tex]-x+7+2r
-5[tex]x^{2}[/tex]+3x+-3 = r
-5[tex]x^{2}[/tex]+2x-7 = 2r
podstawiamy pierwsze rownanie do drugiego
-5[tex]x^{2}[/tex]+2x-7 = 2(-5[tex]x^{2}[/tex]+3x+-3)
-5[tex]x^{2}[/tex]+2x-7 = -10[tex]x^{2}[/tex]+6x-6
5[tex]x^{2}[/tex]-4x-1 = 0
Δ = 16 + 20 = 36
[tex]\sqrt{delta}[/tex] = 6
x1 = [tex]\frac{4+6}{10}[/tex] = 1
x2 = [tex]\frac{4-6}{10}[/tex] = - [tex]\frac{1}{5}[/tex]
no i wystarczy terez pods te x1 i x2 do podanego ciągu(będą 2 ciągi) i koniec ;)
Szczegółowe wyjaśnienie: